Shell variations of Siphonaria gigas (Sowerby, 1825) in response to the effect of wave intensity - A Giraldo-López; C Gómez-Schouben (Ciencias Marinas, 1999)
A factorial sampling was conducted to determine the effect of wave intensity on shell length, height and thickness of the limpet Siphonaria gigas (Sowerby, 1835). The main objective was to distinguish between different wave intensity effects on each shell feature. The sampling was carried out at a sheltered and exposed rocky shore at Utría Cove, on the Pacific coast of Colombia. Wave intensity was found to be a determining factor (P < 0.001) in shell changes, producing short, thick shells on the exposed rocky shore.